Pembelajaran Menulis Teks Berita Menggunakan Media Educaplay - Amalia, Ghaitsa Shofa Putri; Ulfah, Anisa; Zahro, Syifa Khuriyatuz (Social, Humanities, and Educational Studies (SHES): Conference Series, 2025)
Learning to write news texts is an important part of developing language skills for grade VII students. However, in practice, many students have difficulty in composing news texts in a coherent, factual, and correct manner. This study aims to describe the planning, implementation, and learning outcomes of writing news texts using Educaplay media, an interactive digital platform designed to increase student participation and interest in learning. This study uses a qualitative descriptive method with data collection techniques through observation, interviews, documentation, and analysis of students' written work. The teaching module is analyzed to determine the use of digital media in the learning process, while students' writing results are evaluated based on news text assessment guidelines that include structure, language, and clarity of information. The subjects in this study were 22 grade VII students of MTs Tanwiriyah Kalisari in the even semester of the 2024/2025 academic year. The results showed that the use of Educaplay media significantly increased students' enthusiasm, creativity, and ability to write news texts. The average student score reached 80, which is included in the very good category. In conclusion, Educaplay media is effective for use in learning to write news texts and is recommended as an interesting and relevant innovation in Indonesian language learning with current developments.Pembelajaran menulis teks berita merupakan bagian penting dalam pengembangan keterampilan berbahasa siswa kelas VII. Namun, dalam praktiknya, banyak siswa mengalami kesulitan dalam menyusun teks berita secara runtut, faktual, dan sesuai dengan struktur yang benar. Penelitian ini bertujuan untuk mendeskripsikan perencanaan, pelaksanaan, dan hasil pembelajaran menulis teks berita dengan menggunakan media Educaplay, sebuah platform digital interaktif yang dirancang untuk meningkatkan partisipasi dan minat belajar siswa. Penelitian ini menggunakan metode deskriptif kualitatif dengan teknik pengumpulan data melalui observasi, wawancara, dokumentasi, dan analisis hasil karya tulis siswa. Modul ajar dianalisis untuk mengetahui pemanfaatan media digital dalam proses pembelajaran, sedangkan hasil tulisan siswa dievaluasi berdasarkan pedoman penilaian teks berita yang mencakup struktur, kebahasaan, dan kejelasan informasi. Subjek dalam penelitian ini adalah 22 siswa kelas VII MTs Tanwiriyah Kalisari pada semester genap tahun ajaran 2024/2025. Hasil penelitian menunjukkan bahwa penggunaan media Educaplay secara signifikan meningkatkan antusiasme, kreativitas, dan kemampuan siswa dalam menulis teks berita. Rata-rata nilai siswa mencapai 80, yang tergolong dalam kategori sangat baik. Kesimpulannya, media Educaplay efektif digunakan dalam pembelajaran menulis teks berita dan direkomendasikan sebagai inovasi pembelajaran Bahasa Indonesia yang menarik dan relevan dengan perkembangan zaman.